The degradation of municipal solid waste incineration leachate by UV/persulfate and UV/H2O2 processes: The different selectivity of SO4•- and •OH - Pengfei Gan; Yichun Sun; Yunyi Li; Liu, Wen; Jiangyu Ye; Meiping Tong; Jialiang Liang (Chemosphere, 2023)
In this work, the different selectivity of SO4•- and •OH towards municipal solid waste incineration leachates (MSWILs) was studied by a comparative study of UV/persulfate (PS) and UV/H2O2. Results showed SO4•- preferentially mineralized carbon atoms of higher average oxidation state, while •OH showed a two-stage mechanism of partial oxidation and mineralization successively. Electron spin resonance (ESR) analysis showed SO4•- had superior selectivity towards MSWILs than •OH, and Fe(II) would significantly affect the selectivity via forming Fe-MSWILs complex. As the consequence, Fe(II) showed slightly negative effect on UV/PS, but greatly enhanced the performance of UV/H2O2/Fe(II). High concentration of Cl- affected the degradation of non-fluorescent substances by UV/PS, while SO42- and NO3- showed no effect. In contrast, anions showed no effect on UV/H2O2. In addition, •OH preferentially attacked large molecules, but SO4•- showed no selectivity. This study further revealed the selectivity of SO4•- and •OH in the treatment of hypersaline wastewater, and provided theoretical support for the development of targeted technology.
Keywords: Average oxidation state of carbon atoms; comparative study; Molecular weight; Partial oxidation; Radical selectivity